Writing the doctoral thesis differently. Issue 1 (February 2019) - Weatherall, Ruth
Writing a doctoral thesis is a testament to years of anxiety, excitement, confusion, terror and passion. A thesis is, however, much more than just an output of learning. It is a formative process through which a doctoral student learns what it means to be a researcher. The doctoral thesis as a form of academic writing has, however, received scant attention in organisational studies. My decision to write my thesis differently inspired me to think deeply about the conventions and procedures of doctoral writing. How is it that doctoral students write? What conventions govern them? And how could doctoral writing be done differently to expand the boundaries of thought in management? In this article, I give an autoethnographic account of how I wrote my thesis differently to provide the groundwork for doctoral students to reconsider the conventional approach to doctoral writing. Ultimately, I offer guidance and points of reflection for how doctoral students and their supervisors might break with writing conventions and contribute to their learning as emerging management researchers through writing the doctoral thesis differently.